Regional Tidal Modelling Using Tide Gauges and Satellite Altimetry Data in South-West Coast of Turkey - Erkoc, Muharrem Hilmi; Dogan, Ugur (ELSEVIER, 2022)
This study aims to determine the main tidal parameters and the regional tidal model in the south-west coasts of Turkey using the least-squares harmonic estimation method. For this purpose, the sea level data were analyzed and compared to the tides that affect sea level based on the tidal model using the tide gauge station and satellite altimetry data. High-Frequency tide gauge data were obtained from the TUDES (Turkish National Sea Level Monitoring System) data archive and multi-mission satellite altimetry data were achieved from the AVISO data archive. The tidal components of ten tide gauge stations distributed in the south-west coast of Turkey were computed between the period 1998-2018. The results were compared with DTU10 and FES2014b global tide models and regional X-TRACK tidal constants (for Mediterranean). It was found that the differences of the global and regional model solutions were less than 1.3 cm for the main tide constituents (semidiurnal: M-2, S-2 and diurnal: K-1, O-1). Moreover, a regional tidal model for Turkey's south-west coast was determined from tide gauge stations and satellite altimetry. The results indicated that the difference between the two solutions was about 0.8 cm.
Keywords: Tidal modelling; Tide gauge; Satellite altimetry; Sea level; South-west coast of Turkey; VERTICAL LAND MOTION; SEA; GULF; Engineering